The mRNA decay factor PAT1 functions in a pathway including MAP kinase 4 and immune receptor SUMM2. (20th January 2015) - Roux, Milena Edna; Rasmussen, Magnus Wohlfahrt; Palma, Kristoffer; Lolle, Signe; Regué, Àngels Mateu; Bethke, Gerit; Glazebrook, Jane; Zhang, Weiping; Sieburth, Leslie; Larsen, Martin R; Mundy, John; Petersen, Morten
Abstract Multi‐layered defense responses are activated in plants upon recognition of invading pathogens. Transmembrane receptors recognize conserved pathogen‐associated molecular patterns (PAMPs) and activate MAP kinase cascades, which regulate changes in gene expression to produce appropriate immune responses. For example, Arabidopsis MAP kinase 4 (MPK4) regulates the expression of a subset of defense genes via at least one WRKY transcription factor. We report here that MPK4 is found in complexes in vivo with PAT1, a component of the mRNA decapping machinery. PAT1 is also phosphorylated by MPK4 and, upon flagellin PAMP treatment, PAT1 accumulates and localizes to cytoplasmic processing (P) bodies which are sites for mRNA decay. Pat1 mutants exhibit dwarfism and de‐repressed immunity dependent on the immune receptor SUMM2. Since mRNA decapping is a critical step in mRNA turnover, linking MPK4 to mRNA decay via PAT1 provides another mechanism by which MPK4 may rapidly instigate immune responses.